Análise do atendimento ao Código Florestal e a regularização ambiental por unidades de bacias hidrográficas - Gontijo, Gustavo Antomar Batista (2019)
Following the enactment of the New Forest Code (CF), Law no. 12.651/2012, one of the greatest challenges, still to be implemented, is to address conflicts of use of rural properties in order to regularize and maintain them. Studies that present diagnoses on anthropic interventions, in disagreement with legislation, are of paramount importance for the development of preventive and corrective actions. Thus, the objective of this study was to map, quantify and characterize the areas located in the Sub Basin GD2 ‘Vertentes of Rio Grande’, in the state of Minas Gerais, Brazil, in order to evaluate the compliance with the current legislation and indicate which areas should be recomposed or compensated, as a means to assist the public power when adopting mitigating and conservationist measures. The division of the analysis region into ottobacias was used to create basic areas to individually analyze the compliance with the Forest Code. Five classes of soil occupation were mapped: Native Vegetation (20.75%), Reforestation (4.29%), Water mass (0.4%), Urban Area (1.35%) and Anthropogenic Area, 19%). The results showed that the studied area is in agreement with the legislation, since there is enough native vegetation to compensate Legal Reserve of all the properties. However, only 36.15% of the 30 meters of Permanent Preservation Area of watercourses are covered with native vegetation, demonstrating that there are areas that can be regularized by the Environmental Regularization Program, which may further compound the “surplus” of within the Sub Basin. The analysis of the 22 ottobacias showed the regions that contribute with the total native vegetation of the Sub Basin, indicating the priority areas for recovery and the areas with greater potential for the incentive of the application of Quotas of Environmental Reserves. In general, this proposal will contribute to mitigate the impacts generated by Law 12.651/12 on the reduction of protected areas.